Response Of Unmitigated Wheat to Nitrogen And Its Method Of Application - Shekhawat, G S; Kothari, R K; Mehta, M L K (Annals of Arid Zone, 2016)
Toe results of field experiment conducted at Regional Research Station, Basawara during rabi 1967-68 and 1968-69 to study the response of unircigatel4 wheat to nitrogen and its method of application have been discussed. Average yield of grain and straw of wheat increased by 14.5 and 12.5 per cent respectively with' the application of 20 kg N/ha over control. Basal application of nitrogen full in soil gave higher yield than in splits (1/2 as basal + 1/2 as foliar application. Variety Rs. 31-1 proved superior to local wheat